OVARIAN AND HEPATIC BIOCHEMICAL CORRELATIVE CHANGES IN THE FRESHWATER FISH, LABEO BOGGUT (SYKES.) - PATIL, MANOHAR; KULKARNI, R.S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Biochemical contents in the ovary and liver of the freshwater fish, Labeoboggut have been studied during 12 months period and variations are correlated with the reproductive cycle. Ovarian lipid, protein and glycogen gradually increas from maturing phase reaching maximum during mature phase. Hence, they are directly proportional to the reproductive cycle whereas indirectly proportional to the hepatic contents. This reflects utilization of components from the liver for ovarian growth and spawning. Cholesterol increases during maturing phase and decreases in the developed ovar indicating its availability for steriod production during maturing phase for vitellogenesis.